2020
DOI: 10.1016/j.labeco.2020.101925
|View full text |Cite
|
Sign up to set email alerts
|

Shedding light on the shadows of informality: A meta-analysis of formalization interventions targeted at informal firms

Abstract: The Institute of Social Studies is Europe's longest-established centre of higher education and research in development studies. On 1 July 2009, it became a University Institute of the Erasmus University Rotterdam (EUR). Postgraduate teaching programmes range from six-week diploma courses to the PhD programme. Research at ISS is fundamental in the sense of laying a scientific basis for the formulation of appropriate development policies. The academic work of ISS is disseminated in the form of books, journal art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 62 publications
3
43
0
Order By: Relevance
“…Second, our paper adds to the literature on formalization interventions in developing countries, which includes studies in Latin America and South-East Asia reviewed by Bruhn and McKenzie (2014) and Floridi et al (2020), and novel research in Africa by Lediga et al (2020) and Benhassine et al (2018). In particular, we extend the knowledge about how formalization interventions can impact on not only firm registration but also tax-filing compliance, and whether this can be achieved cost-effectively.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Second, our paper adds to the literature on formalization interventions in developing countries, which includes studies in Latin America and South-East Asia reviewed by Bruhn and McKenzie (2014) and Floridi et al (2020), and novel research in Africa by Lediga et al (2020) and Benhassine et al (2018). In particular, we extend the knowledge about how formalization interventions can impact on not only firm registration but also tax-filing compliance, and whether this can be achieved cost-effectively.…”
Section: Introductionmentioning
confidence: 92%
“…Traditional methods, such as tax education campaigns or taxpayer register programmes, are used to enhance taxpaying in developing countries. Several studies have evaluated the impacts of formalization interventions such as business registration programmes and information campaigns on firms' formalization rate, and have found that in general such interventions do not increase the number of formal firms (for literature reviews see e.g., Bruhn and McKenzie 2014;Floridi et al 2020). Most previous studies have examined formalization interventions in Latin America and South-East Asia, and only a few have been conducted in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Despite such efforts, policies fostering business formalization do not seem to achieve the expected transformation (Floridi, Demena, and Wagner 2020). If formalization policies have limited impacts, it is not clear whether those firms opting for formalizing actually gain advantages from switching status.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst meta-analyses have been carried out in several areas of economics and business management (Tingvall and Ljungwall 2012;Demena 2015), few reviews and meta-analyses explore the impact of policy actions on business formalization (Floridi, Demena, and Wagner 2020). To the best of our knowledge, there are no meta-analyses investigating firm performance induced by formalization.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to its common usage, 'formalisation' does not describe a distinct phenomenon, but a set of diverse processes relating to the creation of new institutional linkages between state or formal economic structures and individuals or businesses. 4 As we will show, however, the term is conventionally used to describe and compare, as if they were 1 For reviews and meta-analyses of this expansive literature, see for example Bruhn and McKenzie (2014); Floridi, Demena and Wagner (2020). Where it is motivated in part by a desire to widen the tax base, policy enthusiasm seems likely to increase to address fiscal shortfalls resulting from the Covid-19 pandemic (Gallien and van den Boogaard 2021 forthcoming).…”
Section: Introductionmentioning
confidence: 99%